Imperfection - Grant, Patrick (Cultural Dialectics, 2012)
??aspirations to perfection awaken us to our actual imperfection.? It is in the space between these aspirations and our inability to achieve them that Grant reflects upon imperfection. Grant argues that an awareness of imperfection, defined as both suffering and the need for justice, drive us to an unrelenting search for perfection, freedom, and self-determination. The twenty-one brief chapters of Imperfection develop this governing idea as it relates to the present situation of the God debate, modern ethnic conflicts, and the pursuit of freedom in relation to the uncertainties of personal identity and the quest for self-determination. Known for his exploration of the relationship between Buddhism and violent ethnic conflict in modern Sri Lanka, as well as his contribution to the study of Northern Ireland and the complex relationships among religion, literature, and ethnicity, Grant provides the reader with an analysis of the widespread rise of religious extremism across the globe. Referencing Plato, Van Gogh, Jesus, and the Buddha, he enlightens the reader with both succinct and original insights into human society. Imperfection is the result of an important Canadian public intellectual at work.